Atención de enfermería y su incidencia en enfermedades diarreicas agudas en niños menores de cinco años, en el servicio de consulta externa del Hospital Básico Juan Montalvan Cornejo, Ricaurte octubre 2018– abril 2019 - Moreno Sánchez, Flor Maria (2019)
The present investigation was carried out in the outpatient area of the Juan Montalván Cornejo Basic Hospital of the Urdaneta Canton of the Province of Los Ríos. The causes of acute diarrheal diseases in children under five years of age in this city were studied. The general objective was to learn about the care process carried out by the nursing staff with the purpose of preventing acute diarrheal diseases in children under five years of age in an orderly and controlled manner. The methods that were applied in the investigation are the descriptive and documentary, since they allow to observe, analyze, record facts and actions to obtain real information related to the subject of study. The results obtained: determined that nursing care with adequate techniques and procedures, will reduce acute diarrheal diseases in children under five years of age who attend the outpatient clinic at the Juan Montalván Cornejo Basic Hospital in the city of Ricaurte. Conclusion: there are no adequate strategic plans to reduce the rate of diarrheal diseases in children under five years of age who attend the outpatient clinic of the Juan Montalván Cornejo Basic Hospital in the city of Ricaurte